Escultura para o corpo : Maria José Oliveira - Albuquerque, Isabel Ribeiro (2019)
In this article we intend to analyze a set of works by Maria José Oliveira that are on the border of Sculpture and Jewelry. Since some of these pieces presuppose a body to use them, although they may be autonomous, it will be more appropriate to call this group of works Sculpture for the body. They are mixed pieces, which play with the interior / exterior and the presence / absence of the body. It’s a work in transition constituted by versatile objects that mold to the body, dressing and reconfiguring it